Antibacterial Carbon Dots: Mechanisms, Design, and Applications - Zhao, Wen‐Bo; Liu, Kai‐Kai; Wang, Yong; Li, Fu‐Kui; Guo, Rui; Song, Shi‐Yu; Shan, Chong‐Xin (Advanced healthcare materials, 2023)
The increase in antibiotic resistance promotes the situation of developing new antibiotics at the forefront, while the development of non‐antibiotic pharmaceuticals is equally significant. In the post‐antibiotic era, nanomaterials with high antibacterial efficiency and no drug resistance make them attractive candidates for antibacterial materials. Carbon dots (CDs), as a kind of carbon‐based zero‐dimensional nanomaterial, are attracting much attention for their multifunctional properties. The abundant surface states, tunable photoexcited states, and excellent photo‐electron transfer properties make sterilization of CDs feasible and are gradually emerging in the antibacterial field. This review provides comprehensive insights into the recent development of CDs in the antibacterial field. The topics include mechanisms, design, and optimization processes, and their potential practical applications are also highlighted, such as treatment of bacterial infections, against bacterial biofilms, antibacterial surfaces, food preservation, and bacteria imaging and detection. Meanwhile, the challenges and outlook of CDs in the antibacterial field are discussed and proposed.